The Effect of Ease of Use, Effectiveness, and Perception of Risk on Interest in Using Seabank Digital Bank (A Case Study in Higher Education) - Ramadhani Putri, Habsiah; Trisnaningsih, Sri (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2025)
The development of information technology has driven the rapid growth of Financial Technology (Fintech) services, including digital banking. Ease of use, effectiveness, and transaction security have become the main factors encouraging the adoption of these services, especially among Generation Z, who are known for their adaptability to technology. One of the prominent digital banks among students is Seabank, which is recorded as the most widely used digital bank by accounting students at UPN "Veteran" East Java, with a usage rate reaching 82.9%. The purpose of this study was to analyze how ease of use, effectiveness, and risk perception influence the interest in using SeaBank digital banking among accounting students at UPN “Veteran” East Java. This study employs a quantitative method with the analysis technique of Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). This technique is used to examine the relationships among variables in the research model. Primary data were collected through an online questionnaire distributed via Google Forms to 50 Accounting students (class of 2022–2023) at UPN "Veteran" East Java. The data were analyzed using SmartPLS 4.0 software. The research conducted reveals that the variables of ease of use, effectiveness, and risk perception have a positive and significant impact on the interest in using Seabank digital banks among accounting students at UPN “Veteran” East Java.